1998
DOI: 10.1523/jneurosci.18-04-01622.1998
|View full text |Cite
|
Sign up to set email alerts
|

Fornix Lesions Can Facilitate Acquisition of the Transverse Patterning Task: A Challenge for “Configural” Theories of Hippocampal Function

Abstract: Configural theories of hippocampal function predict that hippocampal dysfunction should impair acquisition of the transverse patterning task, which involves the concurrent solution of three discrimination problems: A+ versus B-; B+ versus C-; and C+ versus A-. The present study tested this prediction in rats using computer-graphic stimuli presented on a touchscreen. Experiment 1 assessed the effects of fornix lesions when the three problems were introduced sequentially (phase 1: A+ vs B-; phase 2: A+ vs B-, B+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 43 publications
3
70
0
Order By: Relevance
“…Also, Rondi-Reig et al (2001) tested mice lacking CA1 NMDA receptors on the transverse patterning problem that required simultaneous acquisition of three odor discriminations comprising the transverse patterning problem contrasted with concurrent learning of three simple odor discriminations. They found that CA1 NMDA receptor knock-out mice were impaired in solving the transverse patterning odor discrimination compared with normal performance on the non-overlapping (elemental) concurrent odor discriminations (but see Bussey et al, 1998). To the best of our knowledge, prior to the present work, the transverse patterning task has not been previously employed in the studies of aged animals.…”
Section: Transverse Patterning Discriminationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, Rondi-Reig et al (2001) tested mice lacking CA1 NMDA receptors on the transverse patterning problem that required simultaneous acquisition of three odor discriminations comprising the transverse patterning problem contrasted with concurrent learning of three simple odor discriminations. They found that CA1 NMDA receptor knock-out mice were impaired in solving the transverse patterning odor discrimination compared with normal performance on the non-overlapping (elemental) concurrent odor discriminations (but see Bussey et al, 1998). To the best of our knowledge, prior to the present work, the transverse patterning task has not been previously employed in the studies of aged animals.…”
Section: Transverse Patterning Discriminationsmentioning
confidence: 88%
“…There have been several reports of anterograde amnesia for the transverse patterning problem after the damage to the hippocampus (Alvarado & Rudy, 1995a,b;Dusek & Eichenbaum, 1998; but see Bussey et al, 1998). For example, Alvarado and Rudy (1995a) found that rats with damage to the hippocampus could not solve the transverse patterning problem, but they readily learned to solve a control set of three elemental discrimination problems.…”
Section: Introductionmentioning
confidence: 99%
“…Dusek and Eichenbaum found that rats with hippocampal damage succeeded in the initial training stages but failed in performing the concurrent random presentations. Bussey et al (21) trained animals in a protocol similar to that of Alvarado and Rudy (20), but presented the stimuli on a touch screen, and found that both normal rats and rats with hippocampal damage gradually acquired the task. One interpretation of these findings is that animals with hippocampal damage can partially succeed or even outperform normal animals whenever they adopt specific response to individual stimuli or stimulus compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the Dusek and Eichenbaum study (12), animals with hippocampal damage might have used other nonrelational strategies that were effective for the pairs presented in an orderly sequence (i.e., always chose the odor that was not previously rewarded, for example), but these strategies did not support performance when the order of pairs was random. In the Bussey et al study (21), the presentation of two-dimensional stimuli on a screen may have encouraged the acquisition of stimulus compounds, and that strategy may have been especially well used by animals with hippocampal damage.…”
Section: Discussionmentioning
confidence: 99%
“…This problem, known as "transverse patterning," [Spence, 1952] is identical to the game "Rock Paper Scissors," in that each stimulus is ambiguous, but by attending to the relations between the stimuli, the problem can be solved. Hippocampal damage has been shown to severely disrupt performance of this task in rats [Alvarado and Rudy, 1995;Dusek and Eichenbaum, 1998; but see Bussey et al, 1998], monkeys [Alvarado et al, 2002], and humans [Reed and Squire, 1999;Rickard and Grafman, 1998], relative to a control condition in which the same stimuli are consistently designated as correct or incorrect regardless of their pairing. Hereafter, we refer to such a control condition as "elemental," while the task condition involving the transverse patterning problem is referred to as "configural" (Fig.…”
Section: Introductionmentioning
confidence: 99%